Tabù e sensibilità: le precauzioni rituali nel candomblé - Francesca Bassi (Archivio Antropologico Mediterraneo)
In the context of the Candomblé of Bahia, ritual prohibitions, called quizilas, play an important role in the making of the symbolic relationship between the initiate and spiritual entities (orixás). Field research opened to the hypothesis that, in addition to the prohibitions associated with the risks of contamination and those of collective nature, there are individual prohibitions based on the sensitivity of the adept. Indeed, many elements associated with negative events experienced by orixás at mythological time produce, at present time, negative reactions in initiates, who may feel disgust, rejection, intolerance, especially towards food. The relationship between the initiate and orixá, therefore, involves a sort of overlapping of identity which is reflected in the initiate’s bodily sensitivity. The study of quizilas therefore indicated the importance of an ethnographic practice focused on the notion of “sensual body”.